Exenatide and dapagliflozin combination improves markers of liver steatosis and fibrosis in patients with type 2 diabetes. Issue 3 (14th December 2019) - Gastaldelli, Amalia; Repetto, Enrico; Guja, Cristian; Hardy, Elise; Han, Jenny; Jabbour, Serge A.; Ferrannini, Ele
Abstract: Aim: To assess the efficacy of exenatide (EXE) once weekly + dapagliflozin once daily (DAPA) versus each drug alone in reducing biomarkers of fatty liver/steatosis and fibrosis in a post hoc analysis of DURATION‐8, a 104‐week study in 695 patients with type 2 diabetes uncontrolled by metformin monotherapy. Materials and methods: We evaluated the impact of the study treatments on non‐invasive markers of hepatic steatosis (fatty liver index [FLI] and non‐alcoholic fatty liver disease [NAFLD] liver fat score), fibrosis (fibrosis‐4 index [FIB‐4]) and severe fibrosis (NAFLD fibrosis score), along with liver enzymes and insulin resistance, at weeks 28 and 52. All outcomes in this analysis were exploratory, with nominal P values reported. Results: At week 28, biomarkers of fatty liver/steatosis and fibrosis were reduced from baseline in all treatment groups. At week 28, EXE once weekly + DAPA effects for decrease in FLI were stronger than those of EXE once weekly + placebo (PLB; −2.92, 95% confidence interval [CI] −5.11, −0.73; P = 0.0092) or DAPA+PLB (−2.77 [95% CI −4.93, −0.62]; P = 0.0119), and stronger than those of EXE once weekly + PLB at week 52 (−3.23 [95% CI −5.79, −0.68]; P = 0.0134). FIB‐4 showed reduction versus baseline only in the EXE once weekly + DAPA group at both week 28 (−0.06 [95% CI −0.11, −0.01]; P = 0.0135) and week 52 (−0.05 [95% CI −0.09, −0.004]; P = 0.0308). Conclusions: The EXE once weekly + DAPA combination showed stronger effects than EXE once weekly + PLB or DAPA + PLB in ameliorating markers of hepatic steatosis and fibrosis in patients with type 2 diabetes. Prospective trials are needed to validate these findings.